Goal setting in the mechanism of public-legal regulation of finance - Anatoly Selyukov, Imeda Tsindeliani,; Bochkareva, Ekaterina; Mironova, Svetlana (Opción, 2019)
The objective of this article is to determine the nature of goal-setting as an integral part of the mechanism of public legal regulation, the factor and the criterion of the effectiveness of its functioning via the structural-functional method. As a result, it is recognized that the implementation of legal support for the activities of subjects in the sphere of public finance is not sufficient only by means of procedural aspects. In conclusion, there is a need to specify the purpose of legal regulation in the texts of financial laws and the subsequent definition of criteria for achieving the goals fixed.